(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Unilateralità e/o bilateralità dei provvedimenti Covid-19 e libertà della Chiesa - 2. L’esercizio della libertà religiosa di fronte alla pandemia - 3. Gli atti rituali nell’era del Covid-19 - 4. La dimensione territoriale della religione. The Pope and the challenge of the pandemic ABSTRACT: The measures taken to tackle the pandemic, although taken unilaterally by the State, were shared by the ecclesiastical authority without giving rise to disputes. Pope Francis unilaterally adopted ways of celebrating the rites and administering the sacraments in order to protect life. His innovative use of the media has updated the language, the forms of celebration of the rites and collective participation of the Catholic faithful, arousing perplexity in some faithful who complain about violations of religious freedom and the principle of bilaterality in Church-State relations.